Effects of Parental Engagement on the Academic Performance Of Grade One Pupils - Librea, Joy Lyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the extent of the effects of parental engagement on the academic performance of Grade One pupils in selected public elementary schools in Baras District, Schools Division Office of Rizal, during the School Year 2025–2026. Specifically, it examined parental engagement in terms of communication, learning support at home, participation in school activities, and monitoring and feedback, as perceived by teachers and parents, and investigated whether these variables were associated with pupils’ academic performance. The study employed a descriptive survey research design complemented by documentary analysis. Respondents consisted of 36 Grade One teachers and 150 parents from Baras Elementary School, Baras Pinugay Elementary School, Baras Pinugay Phase 2 Elementary School, Evangelista Elementary School, and Santiago Elementary School. A researcher-made questionnaire-checklist served as the primary data-gathering instrument, while pupils’ average grades were obtained through documentary analysis to determine academic performance. Descriptive and inferential statistical tools were used to analyze the data. Findings revealed that teachers perceived parental engagement as having a high effect on pupils’ academic performance, whereas parents rated its effect as very high. Significant differences existed between teachers’ and parents’ perceptions regarding learning support at home and monitoring and feedback, while no significant differences were found in communication and participation in school activities. Teachers’ demographic profiles showed no significant influence on their perceptions, whereas parents’ educational attainment and occupation significantly affected their views, unlike age, sex, number of children, and monthly family income. Documentary analysis further showed that Grade One pupils achieved a satisfactory level of academic performance. However, no significant relationship was found between the perceived extent of parental engagement and pupils’ academic performance. The study concluded that although parental engagement is widely recognized by teachers and parents as beneficial to pupils’ learning, its perceived influence does not directly translate into higher academic achievement. It is therefore recommended that school administrators strengthen parent education programs, teachers sustain regular communication and home-learning support initiatives, and parents actively collaborate with schools in monitoring pupils’ progress. Implementation of the proposed action plan and further studies involving additional variables are likewise recommended.